Judging Close Corporations in the Age of Statutes - Ian Ayres (Washington University Law Quarterly, 1992)
This Article examines the interaction between courts and legislatures in developing the law that governs close corporations.
Keywords: Close corporations; Economics & corporation law; Common law; Statutes